Integration of an Energy Storage in Connection with the Combustion Chamber of a Diesel Engine to Reduce the NOx Emission - Dion Arman Lilipaly; Karsten Wehner; Steffen Loest (International Journal of Marine Engineering Innovation and Research, 2018)
NOx is one of the chemical compound that contained in the acid rain. It is not only bad for human health but it also effected the environment for instances lake acidification. To overcome that problem, IMO made a regulation that controls the NOx emission that forced the shipping company to reduce their NOx pollution in certain areas. Hence, a new technology or method are needed to comply with those IMO Tier regulations. A new idea has been proposed that could reduce the combustion temperature by integrating an external chamber connected with the combustion chamber as a temporary energy storage. This method is implementing the pressure-temperature law, where the pressure is reduced by expanding the volume that resulted a temperature decreased. The aims of this study were to make a combustion model simulation and technical drawings design of the external chamber. The simulation model involves an analysis of how the temporary energy stored effected the combustion temperature and calculating the pipeline losses. The results showed that by installing the external chamber, the combustion temperature was reduced significantly by 6.15% for the burn zone and 17.8% for the unburn zone. Furthermore, a comparison of the pipeline heat loss showed that an insulated pipe saved 99.6% more heat energy than the uninsulated.